Female Short Shoot and Ovule Development in Ginkgo biloba L. with Emphasis on Structures Associated with Wind Pollination. (28th August 2012) - Jin, Biao; Wang, Di; Lu, Yan; Jiang, Xiao Xue; Zhang, Min; Zhang, Lei; Wang, Li
Abstract : The orientation and morphology of the female cone are important for wind pollination in gymnosperms. To examine the role of female reproductive structures associated with wind pollination in Ginkgo biloba, we used scanning electron microscopy and semithin section techniques to observe the development of female short shoots and ovules in G. biloba before and during the pollination period. The ovule differentiation process was divided into six stages: undifferentiated, general stalk differentiation, integument differentiation, nucellus differentiation, collar differentiation, and mature stage. Before the pollination period, the integument tip generated the micropylar canal and the micropyle, while the nucellus tip cells degenerated to form the pollen chamber. During pollination, the micropylar canal surface became smooth, the micropyle split into several pieces and bore a pollination drop, and the pollen chamber directly faced the straight micropylar canal. The leaves and ovules were spirally arranged on the female short shoot, with the ovules erect and the fan-shaped leaves bent outwards and downwards. The ovules of G. biloba have differentiated some special architectural features adapted for pollen capture and transport. Together, these structures constitute a reproductive structural unit that may improve wind pollination efficiency at the female level.